Arah Baru Pembelajaran Berbicara Bahasa Arab (Inovasi Buku Ajar Berbasis Metode Visualization, Auditory, Kinestetic - Aulia, Annisa; Mukmin, Mukmin; Irmansyah, Irmansyah; Ubaidillah, Ahmad; Heriani, Fadhilah (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2025)
ملخص البحث: تهدف هذه الدراسة إلى تطوير كتاب مدرسي للغة العربية يعتمد على طريقة البصرية والسمعية والحركية (VAK) لتحسين مهارة الكلام لطلاب بالمدرسة المتوسطة الحكومية الأولى باليمبانج. وقد تم تطوير كتاب المدرسي الكلام على خلفية مشكلة نظام التعلم استنادًا إلى الملاحظات والمقابلات وبيانات الاستبيانات التي قام بها الباحثة من قبل، والتي توضح مشاكل التعلم المختلفة مثل عدم وجود دافعية لدى الطلاب في المشاركة في الدروس، وشعور الطلاب بالملل في التعلم، وقلة نشاط الطلاب في الفصل، وخطوات التعلم التي لا تتفق مع الأهداف المراد تحقيقها في الكتاب المدرسي، والأساليب التي لا تتفق مع أساليب التعلم لدى الطلاب، والخلفيات التعليمية المختلفة للطلاب، مما يؤثر على طريقة فهمهم واستيعابهم للتعلم. المنهجية المستخدمة في هذا البحث هي البحث والتطوير باستخدام نموذج التطوير ADDIE، أي التحليل والتصميم والتطوير التنفيذ والتقويم. حصلت نتائج التحقق من صلاحية المنتجات التي تم تطويرها بناء على خبراء المواد على درجة 80%، ثم بناء على خبراء الإعلام على درجة 87.5% بفئة”صالح جداً“، بينما حصلت نتائج اختبار فعالية المنتج للاختبار القبلي على قيمة 52.3% وبعد استخدام المنتج شهدت زيادة في قيمة الاختبار البعدي بلغت 81.07%، ثم بالنسبة لاستجابة المعلم للكتاب المدرسي الذي تم تطويره حصل على نسبة 81.25% وحصل استبيان رضا الطلاب على نتيجة 86. 9٪ بفئة جيد جداً أو صالح جداً، لذلك فإن تطوير كتاب المدرسي الكلام القائم على طريقة البصرية والسمعية والحركية (VAK) مؤثر في تحسين مهارة الكلام عند الطلاب. ABSTRACT: This study aims to develop an Arabic textbook based on the VAK method (Visualization, Auditory, Kinestetic) in an effort to improve the kalam proficiency of class VII students of MTS N 1 Palembang. The development of kalam textbooks is carried out against the background of learning system problems based on observations and interviews as well as questionnaire data that researchers have done before, explaining various learning problems such as lack of student motivation in participating in lessons, students feel bored in learning, students are less active in class, learning steps that are not in accordance with the objectives to be achieved in the textbook, methods that are not in accordance with students' learning styles and various educational backgrounds of students, thus affecting the way they understand and absorb learning. The methodology used in this research is research and development or R and D with the ADDIE development model, namely analysis, design, development, trial or implementation and evaluation. The results of the validation of the products that have been developed based on material experts get a score of 80% then based on media experts get a score of 87.5% with the category “very feasible”, while the results of the product effectiveness test for the pre test obtained a value of 52.3% and after using the product experienced an increase in the post test value of 81.07%, then for the teacher's response to the textbook that has been developed, get a score of 87.5% with the category “very feasible”. while the results of the product effectiveness test for the pre test obtained a value of 52.3% and after using the product experienced an increase in the post test value of 81.07%, then for the teacher's response to the textbook that has been developed, getting a percentage of 81.25% and a student satisfaction questionnaire obtained a result of 86.9% with a very good or valid category, so that the development of this VAK (Visualization, Auditory, Kinestetic) method-based kalam textbook has an effect in improving maharoh kalam in students. Keywords: textbooks, VAK method (visualization, auditory, kinestetic), maharoh kalam, addie model ABSTRAK: Penelitian ini memiliki tujuan yaitu mengembangkan sebuah buku ajar bahasa arab berbasis metode VAK (Visualization, Auditory, Kinestetic) dalam upaya peningkatan kemahiran kalam siswa kelas VII MTS N 1 Palembang. Pengembangan buku ajar kalam ini dilakukan dengan latar belakang masalah sistem pembelajaran yang berdasarkan observasi dan wawancara serta data angket yang telah peneliti lakukan sebelumnya, menjelaskan berbagai problem masalah pembelajaran seperti minimnya motivasi siswa dalam mengikuti pelajaran menyebabkan mereka merasa jenuh saat belajar., siswa kurang aktif dikelas, proses pembelajaran yang diterapkan tidak sejalan dengan target yang ingin dicapai dalam buku ajar, metode ajar yang tidak selaras dengan cara belajar siswa serta latar belakang pendidikan siswa yang bermacam-macam, sehingga mempengaruhi cara mereka memahami dan menyerap pembelajaran. Metodologi yang digunakan dalam penelitian ini adalah research and development atau R and D dengan model pengembangan ADDIE, yaitu analisis, desain, pengembangan, uji coba atau implementasi dan evaluasi. Hasil validasi produk yang telah dikembangkan berdasarkan ahli materi mendapatkan sekor 80% kemudian berdasarkan ahli media mendapat skor 87,5% dengan kategori “sangat layak”, sedangkan hasil uji keefektifitasan produk untuk pre test memperoleh nilai sebesar 52,3% dan setelah menggunakan produk mengalami peningakatan pada nilai post test sebesar 81,07%, kemudian untuk respon guru terhadap buku ajar yang dikembangkan peneliti ini, mendapatkan persentase sebesar 81,25% dan angket kepuasan siswa memperoleh hasil sebesar 86.9% dengan kategori sangat baik atau valid, sehingga pengembangan buku ajar kalam berbasis metode VAK (Visualization, Auditory, Kinestetic) ini berpengaruh dalam meningkatkan maharoh kalam pada siswa. Kata kunci : buku ajar, metode vak (visualization, auditory, kinestetic), maharoh kalam, model addie